2010
DOI: 10.1161/hypertensionaha.109.148171
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Activity-Modifying Protein 1 Increases Baroreflex Sensitivity and Attenuates Angiotensin-Induced Hypertension

Abstract: Abstract-Calcitonin gene-related peptide (CGRP) is a powerful vasodilator that interacts with the autonomic nervous system. A subunit of the CGRP receptor complex, receptor activity-modifying protein 1 (RAMP1), is required for trafficking of the receptor to the cell surface and high-affinity binding to CGRP. We hypothesized that upregulation of RAMP1 would favorably enhance autonomic regulation and attenuate hypertension. Blood pressure, heart rate, and locomotor activity were measured by radiotelemetry in tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 52 publications
2
74
0
Order By: Relevance
“…The use of RAMP1 transgenic mice revealed that CGRP has an early protective effect at the level of the baroreceptors and cerebral vasculature in a similar AngII hypertension model. 16,27 Our present results indicate a much wider potential of CGRP and its receptors to protect against the onset and maintenance of AngII-induced hypertension.Analysis of MRVs after 28 days revealed similar vascular reactivity in all treatments with no loss of …”
mentioning
confidence: 56%
See 2 more Smart Citations
“…The use of RAMP1 transgenic mice revealed that CGRP has an early protective effect at the level of the baroreceptors and cerebral vasculature in a similar AngII hypertension model. 16,27 Our present results indicate a much wider potential of CGRP and its receptors to protect against the onset and maintenance of AngII-induced hypertension.Analysis of MRVs after 28 days revealed similar vascular reactivity in all treatments with no loss of …”
mentioning
confidence: 56%
“…13 Evidence indicates the importance of CGRP in aggressive models of rodent hypertension that are centered on the kidney. 14,15 By comparison, there is little evidence of detailed analysis involving the ongoing influence of endogenous CGRP on hypertensive mechanisms and vascular remodeling, especially with regard to NO and oxidative stress pathways.Sensory nerve-derived CGRP release is stimulated by mechanisms that include angiotensin II (AngII) and sympathetic nerve reflexes, 3,4 baroreflex sensitivity, 16 and sensory nerve activators. 17,18 We have investigated the AngII hypertension model in wild-type (WT) and αCGRP knockout (αCGRPKO) mice that have similar resting BP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ubiquitously, were reported to show markedly attenuated responses to angiotensin II-induced hypertension [57] . The pressor response to the CGRP receptor antagonist, CGRP8-37, was greater in RAMP1 Tg mice than in WT mice, confirming a greater antihypertensive action of endogenous CGRP in RAMP1 Tg mice.…”
Section: Phenotypes Of Ramp1 and Ramp3 Knockout Micementioning
confidence: 99%
“…2 Using a model of hypertension produced by systemic administration of angiotensin II, we found that increased expression of RAMP1 greatly reduced the pressor response to angiotensin II. 3 Mechanisms that appeared to contribute to this effect included alterations in baroreflex sensitivity, sympathetic outflow, and sympathetic-mediated vasoconstriction. 3 Although many specifics regarding the pathways involved remain to be defined, these findings support the concept that CGRP and RAMP1 interact with the autonomic nervous system in a manner that protects against hypertension.…”
Section: Response To Letter By Tsudamentioning
confidence: 99%